2011
DOI: 10.1007/s10653-011-9438-7
|View full text |Cite
|
Sign up to set email alerts
|

Pyrite-driven reactive oxygen species formation in simulated lung fluid: implications for coal workers’ pneumoconiosis

Abstract: The origin of coal worker's pneumoconiosis (CWP) has been long debated. A recent epidemiological study shows a correlation between what is essentially the concentration of pyrite within coal and the prevalence of CWP in miners. Hydrogen peroxide and hydroxyl radical, both reactive oxygen species (ROS), form as byproducts of pyrite oxidative dissolution in air-saturated water. Motivated by the possible importance of ROS in the pathogenesis of CWP, we conducted an experimental study to evaluate if ROS form as by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 44 publications
6
37
0
Order By: Relevance
“…It is possible that the dissolution and release of iron is limited in the more complex fluids used in the cellular studies, similar to earlier results with pyrite, which showed a reduction in dissolution rate (Harrington et al, 2012a). Furthermore, at a neutral pH, ferric iron-hydroxide coatings dominate the surface of arsenopyrite and sulfur, not iron, is readily released into solution (Asta et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It is possible that the dissolution and release of iron is limited in the more complex fluids used in the cellular studies, similar to earlier results with pyrite, which showed a reduction in dissolution rate (Harrington et al, 2012a). Furthermore, at a neutral pH, ferric iron-hydroxide coatings dominate the surface of arsenopyrite and sulfur, not iron, is readily released into solution (Asta et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…An excessive particle burden can cause an array of pulmonary issues, ranging from chronic inflammation and fibrosis, to the development of tumors (Oberdorster, 1995). Once inhaled, a mineral particle might undergo surface-mediated reactions, including dissolution reactions (Fubini, 1997; Ghiazza et al, 2011; Harrington et al, 2012a; Schoonen et al, 2006). The reactivity of an inhaled particle is a function of its stability in the lung environment, its solubility, and modifications of its surface, such as the presence of defects or surface coatings (Fubini, 1997; Ghiazza et al, 2011; Schoonen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulated lung fluid (SLF) method used a modified Gambles' solution developed by Takayka (7)(8)(9)(10)(11)(12)(13). Bioaccessibility is determined based on metal release normalized to total metals determined from Aqua Regia extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its diverse roles in the natural and anthropogenic sulfur cycle, pyrite has been extensively studied in various experimental investigations of the kinetics of its dissolution and oxidation [9][10][11][12][13][14][15][16], the isotopic fractionations associated with these reactions [17][18][19][20][21][22], the microbiological processes involved [23][24][25], and the effect of pyrite surface reactivity and hydroxyl radical formation on human health [26][27][28][29]. Common to many of these studies is the pretreatment of pyrite to prevent experimental artifacts and inaccuracies.…”
Section: Introductionmentioning
confidence: 99%